La rima de mèrit a l’Espill de Jaume Roig. - Cantavella, Rosanna (Scripta, 2021)
An appraisal of the rhyme types applied by author Jaume Roig in his Espill (1460), via a quantification of each kind of rhyme of a praiseworthy character (rhymes superior to the basic sonança lleial) in a total of 8104 rhymes (a table of absolute and percentual values is given in annex 1). Results clearly show a high degree of occurrence of praiseworthy rims acordants (57.8% of total rhymes) and within those, of lleonismitat in its different types (46.4%), especially with feminine endings. Diccional rhymes are also analysed, and within them rims equívocs contrafets tipus 3 are highlighted as the most used of this group (7.5%). Roig’s use of homonym rhymes (rims equívocs lleials, of which a list is given in annex 2) is studied too, and attention is paid to potential irregularities, of which Roig only incurs in rims utrisonants, or rhyme of words with a different openness of vowels e and o, of which another list is given in annex 2.